2007
DOI: 10.1016/j.cub.2007.03.039
|View full text |Cite
|
Sign up to set email alerts
|

Endosymbiont-Dependent Host Reproduction Maintains Bacterial-Fungal Mutualism

Abstract: Bacterial endosymbionts play essential roles for many organisms, and thus specialized mechanisms have evolved during evolution that guarantee the persistence of the symbiosis during or after host reproduction. The rice seedling blight fungus Rhizopus microsporus represents a unique example of a mutualistic life form in which a fungus harbors endobacteria (Burkholderia sp.) for the production of a phytotoxin. Here we report the unexpected observation that in the absence of endosymbionts, the host is not capable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
218
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 219 publications
(223 citation statements)
references
References 33 publications
(36 reference statements)
3
218
0
Order By: Relevance
“…This means that external selecting pressures acting on the symbiosis rather than intrinsic control mechanisms of the host have prevented B. rhizoxinica from turning into a parasitic symbiont by losing its biosynthetic capability. Considering that diffusible low-molecular-weight metabolites do not seem to mediate sporulation (Partida-Martinez et al, 2007b), our results are in agreement with a model where the sporulation trigger itself is secreted by the type III apparatus. We propose that the endosymbionts have acquired or mimic a host factor that is necessary to launch its vegetative reproduction program.…”
Section: W T W T + H O S T W T W T + H O S T W T W T + H O S T Orfsupporting
confidence: 90%
See 2 more Smart Citations
“…This means that external selecting pressures acting on the symbiosis rather than intrinsic control mechanisms of the host have prevented B. rhizoxinica from turning into a parasitic symbiont by losing its biosynthetic capability. Considering that diffusible low-molecular-weight metabolites do not seem to mediate sporulation (Partida-Martinez et al, 2007b), our results are in agreement with a model where the sporulation trigger itself is secreted by the type III apparatus. We propose that the endosymbionts have acquired or mimic a host factor that is necessary to launch its vegetative reproduction program.…”
Section: W T W T + H O S T W T W T + H O S T W T W T + H O S T Orfsupporting
confidence: 90%
“…Quite unexpectedly, we observed that the host is not capable of vegetative reproduction in the absence of endosymbionts. However, after reinfection of the fungal host, we observed endobacteria migrate into sporangia, enter vegetative spores of Rhizopus and survive therein until germination (Partida-Martinez et al, 2007b). This unique symbiont-dependent sporulation is an elegant way to prevent formation of symbiont-free spores, thus securing the persistence of the symbiosis.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…However, the bacterial biosynthesis of the toxin rhizoxin is crucial for fungal pathogenicity toward rice seedlings and therefore to the fungal exploitation of plant-derived carbon and nitrogen (298). R. microcarpus also requires B. rhizoxinica for vegetative reproduction (299).…”
Section: Bacterial-fungal Molecular Interactions and Communicationmentioning
confidence: 99%
“…Bacteria stimulate spore germination in several fungi, including the plant-pathogenic oomycete Phytophthora alni (68), the saprophytic cheese-associated fungus Penicillium roqueforti (152), several bark beetle fungal symbionts (1), and the arbuscular mycorrhizal fungus Glomus intraradices Sy167 (161,162). Interestingly, antibiotic treatment to "cure" Rhizopus of the Burkholderia endobacteria living within its hyphae results in a fungus that no longer produces reproductive sporangia or spores (299). This is believed to be a mechanism that ensures the presence of bacteria within fungal spores during vegetative reproduction, guaranteeing the vertical transmission of the bacteria (299), and thus is likely to have been essential for spreading the symbiosis globally (205).…”
Section: Consequences Of Bacterial-fungal Interactions For Participatmentioning
confidence: 99%